CERDAS GIZI: Optimalisasi Pemanfaatan Pangan Lokal dalam Pemberian Makanan Tambahan untuk Pencegahan Risiko Stunting di Desa Bangkonol, Kabupaten Pandeglang - Budiono, Jane Sidney; Sabrilla, Talitha Nasywa; Sari, Wida Puspita; Fauzi, Oktavian; Aprila, Ramanda Karina; Arunita, Ananda Rachmania; Adriansyah, Zidan; Safei, Dio Rizky; Taufik, Epi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Stunting is one of the main chronic nutritional problems in Indonesia. Stunting can be addressed through education on balanced nutrition, stunting prevention, and supplementary feeding interventions (PMT). The Cerdas Gizi program aims to prevent and reduce stunting rates, create sustainable food security, and strengthen community self-reliance through the use of cassava as a local food source. This activity was conducted at the Telaga Biru Posyandu in Bangkonol Village, targeting posyandu cadres, pregnant women, and mothers with infants, with a total of 170 participants. The activity combined theoretical and practical educational approaches through interactive presentations, distribution of informational leaflets, demonstrations of cassava-based supplementary food preparation, and distribution of PMT menu books. The Cerdas Gizi program demonstrated significant improvement, evident in the active participation of partners in the supplementary food preparation process. Additionally, the active participation of the target group in the counseling sessions showed an increase in curiosity about preventing the risk of stunting in children. However, there were challenges during program implementation, including a lack of knowledge among some mothers about the importance of balanced nutrition and difficulties in maintaining consistent visits to the health post. Therefore, continued support is needed through ongoing guidance, regular education, and the utilization of local foods to optimize efforts in preventing stunting.